Medical insurance and free choice of physician shape patient overtreatment: A laboratory experiment - Steffen Huck; Gabriele Lünser; Florian Spitzer; Jean-Robert Tyran (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
In a laboratory experiment designed to capture key aspects of the interaction between physicians and patients, we study the effects of medical insurance and competition in the guise of free choice of physician, including observability of physicians' market shares. Medical treatment is an example of a credence good: only the physician knows the appropriate treatment, the patient does not. Even after a consultation, the patient is not sure whether he received the right treatment or whether he was perhaps overtreated. We find that with insurance, moral hazard looms on both sides of the market: patients consult more often and physicians overtreat more often than in the baseline condition. Competition decreases overtreatment compared to the baseline and patients therefore consult more often. When the two institutions are combined, competition is found to partially offset the adverse effects of insurance: most patients seek treatment, but overtreatment is moderated.
Keywords: C91; I11; I13; 330; Credence good; Physician; Overtreatment; Competition; Insurance